Mapping and analysis of the 2024 Brazil record flooding with Multi-Satellite Data - Donglian Sun; Lihang Zhou; Sanmei Li; Tianshu Yang; Meng Yuan; Andrew Lomax (Geomatics, Natural Hazards & Risk)
During May 2024, Brazil experienced severe flooding due to heavy rainfall associated with low-pressure systems impacting the state of Rio Grande do Sul. This study analyzed operational VIIRS (Visible Infrared Imaging Radiometer Suite) flood products at the original 375-m spatial resolution and downscaled VIIRS floodwater depth at 30-m resolution derived from the original VIIRS flood products using a downscaling model. The analysis indicated several key findings: (1) The operational VIIRS flood products provided flooding information consistent with the flood extent maps from the Emergency Response Coordination Centre (ERCC); (2) The VIIRS downscaled floodwater depth at 30-m resolution provided high resolution equivalent to SAR (Synthetic Aperture Radar) and allied well with the SAR-based flood extent in the South-eastern region of the state, while maintaining VIIRS’s advantage of large spatial coverage; (3) The 3D maps of VIIRS operational flood products at the original 375-m resolution and the downscaled VIIRS floodwater depth at 30-m resolution revealed that flooding is highly related to surface elevation and slope; and (4) Quantitative analysis of the VIIRS downscaled flood map and SAR flood extents indicates an overall accuracy of 80%, a precision of 61%, a recall of 91%, and an F1 score of 73%.